2000
DOI: 10.1053/eupc.1999.0063
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy with an ICD and a documented ICD discharge

Abstract: We report a successful pregnancy in a patient affected by idiopathic ventricular fibrillation 3 years after insertion of an ICD, with a documented defibrillator discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…15) In the last years, only a few studies of ICD therapy during pregnancy have found that the majority of women completed and tolerated pregnancy and delivered without serious complications. 15,[28][29][30] Thus, ICD placement should be considered in pregnant woman with ARVC to prevent episodes of SCD.…”
Section: Discussionmentioning
confidence: 99%
“…15) In the last years, only a few studies of ICD therapy during pregnancy have found that the majority of women completed and tolerated pregnancy and delivered without serious complications. 15,[28][29][30] Thus, ICD placement should be considered in pregnant woman with ARVC to prevent episodes of SCD.…”
Section: Discussionmentioning
confidence: 99%
“…The automatic application of shock in pregnant women already bearer of ICD did not cause maternal or fetal effects [4,5]. Moreover, the real need for intraoperative defibrillation test is object of controversy.…”
Section: A B Discussionmentioning
confidence: 99%
“…Despite its low prevalence, HCM is an important cause of SCD in young individuals [1][2][3][4][5][6]. The main risk factors for fatal arrhythmias in these patients are a history of sudden death in young relatives, the presence of syncope of unknown origin, hypotension during exercise, ventricular septal thickness of e" 30 mm and episodes of NSVT on Holter of 24 hours [1][2][3]6].…”
Section: A B Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Problems are often related to the use of antiarrhythmic drugs. 7 Discontinuation of antiarrhythmic therapy during pregnancy can be the cause of recurrences as well.…”
Section: Pregnancymentioning
confidence: 99%